A family of flexible two-dimensional semiconductors: MgMX2Y6 (M = Ti/Zr/Hf; X = Si/Ge; Y = S/Se/Te). (1st April 2023) - Yuan, Junhui; Xue, Kanhao; Miao, Xiangshui; Ye, Lei
Abstract: Inspired by the recently predicted 2D MX2 Y6 (M = metal element; X = Si/Ge/Sn; Y = S/Se/Te), we explore the possible applications of alkaline earth metal (using magnesium as example) in this family based on the idea of element replacement and valence electron balance. Herein, we report a new family of 2D quaternary compounds, namely MgMX2 Y6 (M = Ti/Zr/Hf; X = Si/Ge; Y = S/Se/Te) monolayers, with superior kinetic, thermodynamic and mechanical stability. In addition, our results indicate that MgMX2 Y6 monolayers are all indirect band gap semiconductors with band gap values ranging from 0.870 to 2.500 eV. Moreover, the band edges and optical properties of 2D MgMX2 Y6 are suitable for constructing multifunctional optoelectronic devices. Furthermore, for comparison, the mechanical, electronic and optical properties of In2 X2 Y6 monolayers have been discussed in detail. The success of introducing Mg into the 2D MX2 Y6 family indicates that more potential materials, such as Ca- and Sr-based 2D MX2 Y6 monolayers, may be discovered in the future. Therefore, this work not only broadens the existing family of 2D semiconductors, but it also provides beneficial results for the future.